Glucose-6-phosphate dehydrogenase correlates with tumor immune activity and programmed death ligand-1 expression in Merkel cell carcinoma. Issue 2 (23rd December 2020) - Nakamura, Motoki; Nagase, Kotaro; Yoshimitsu, Maki; Magara, Tetsuya; Nojiri, Yuka; Kato, Hiroshi; Kobayashi, Tadahiro; Teramoto, Yukiko; Yasuda, Masahito; Wada, Hidefumi; Ozawa, Toshiyuki; Umemori, Yukie; et al.
Abstract : Background: Merkel cell carcinoma (MCC) is a rare and highly malignant skin cancer. Some cases have a good prognosis and spontaneous regression can occur. Reported prognostic markers, such as Merkel cell polyoma virus infection or programmed death ligand-1 (PD-L1) expression, remain insufficient for precisely estimating the vastly different patient outcomes. We performed RNA sequencing to evaluate the immune response and comprehensively estimate prognostic values of immunogenic factors in patients with MCC. Methods: We collected 90 specimens from 71 patients and 53 blood serum samples from 21 patients with MCC at 10 facilities. The mRNA was extracted from formalin-fixed paraffin-embedded tissues. Next-generation sequencing, immunohistochemical staining and blood serum tests were performed. Results: Next-generation sequencing results classified MCC samples into two types: the 'immune active type' was associated with better clinical outcomes than the 'cell division type'. Expression of the glucose-6-phosphate dehydrogenase (G6PD) gene was highly significantly upregulated in the 'cell division type'. Among 395 genes, G6PD expression correlated with the presence of lymph node or distant metastases during the disease course and significantly negatively correlated with PD-L1 expression. Immunohistochemical staining of G6PD also correlated with disease-specific survival and exhibited less heterogeneity compared with PD-L1 expression. G6PD activity could be measured by a blood serum test. The detection values significantly increased as the cancer stage progressed and significantly decreased after treatment. Conclusions: G6PD expression was an immunohistochemically and serum-detectable prognostic marker that negatively correlated with immune activity and PD-L1 levels, and could be used to predict the immunotherapy response.